SOCIOLOGICAL ANALYSIS OF NARCOTICS CIRCULATION TREATMENT ON STUDENTS - Andri Winjaya Laksana (UNISSULA, 2021)
Narcotics abuse is a serious problem experienced by various countries including Indonesia. The proliferation of narcotics trafficking among students has become increasingly alarming by making students the target of narcotics syndicates networks. The concern about the circulation of Narcotics among students must be anticipated immediately considering that students are the next generation of the Nation. Juridical empirical approach method. The implementation of the prevention of narcotics crime among students in its development has not been able to run effectively this is because the circulation of narcotics among students with target consumers of fellow students uses social media networking facilities via the internet which is the result of advances in information and communication technology as well as overcoming the circulation of narcotics crime is divided into : primary, before abuse occurs, or known as a preventive function. Usually in the form of education, dissemination of information about the dangers of drugs, approaches through the family, etc. In carrying out this function, the efforts that must be made by the government include regular outreach, establishment of supervisory institutions, forming laws and regulations in various forms, and even establishing international cooperation both bilaterally, regionally and multilaterally.